ALKELIN: Pelatihan Pengolahan Sampah Pantai Menjadi Eco-paving dan Eco-brick pada Karang Taruna Tunas Muda, Ampenan Selatan. - Hidayanti, Ermia; Lestari, Kurnia; Pratiwi, Sriana; Nurabila, Laylin; Maisaroh, Siti; Priangka, Nabila Aulia (Universitas Mataram, 2024)
The Environmental Awareness Action Program (ALKELIN) held at Skip Ampenan Selatan Beach is a training on processing beach waste into eco-paving and eco-bricks for the purpose of developing ecotourism at Skip Ampenan Selatan Beach through empowering Karang Taruna. This program is motivated by the problem of plastic waste piling up at Skip Ampenan Selatan Beach and the lack of knowledge and skills of the community in managing plastic waste and marketing the beach's tourism potential. The ALKELIN program, which was implemented for 3 months, took the form of training for Karang Taruna members on processing plastic waste into economically valuable products such as eco-paving and eco-bricks. Apart from that, the aim of this program is to promote Skip Ampenan Selatan Beach as an environmentally friendly tourist destination. The results of this program show an increase in the knowledge and skills of Karang Taruna members in processing plastic waste and marketing the potential of beach tourism. Apart from that, this program has also produced economically valuable products from plastic waste and increased the number of visitors to Skip Ampenan Selatan Beach. The ALKELIN program shows that community empowerment, especially Karang Taruna, through training and mentoring can be an effective solution for developing ecotourism and overcoming the problem of plastic waste.